A New Structure of the Nine Level Inverter Used as Active Power Filter with a Reduced Number of Swiches - Fethi Chouaf; Salah Saad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
In the scope of this work, a new structure of the nine level inverter is proposed using a reduced number of power switches. This inverter is used as a shunt active power filter to compensate harmonic currents and the reactive power. The modeling and simulation of the proposed model were carried out in Matlab/Simulink environment. The simulation results show that the filtering performances were achieved despite the reduction of the switches number. It was found that the current waveform becomes purely sinusoidal with a reduction in the harmonic distortion rate (THD) to 2.68%. This implies good compensation of both harmonics and reactive power with a power factor closer to unity. Reducing the switches number allows reducing the switching losses and lowering the duration of the applied voltage supported by the semiconductors. The proposed topology also allows to get simple structure of the inverter with a reduced cost.